Penerapan Metode Talaqqi dalam Menghafal Al-Qur’an dan Implikasinya terhadap Kekuatan Hafalan pada Pelajar Boarding School di SMP Menara Al-Qur’an Parakan - Hakim, Alwi; Hammam, Hammam (CV. Creative Tugu Pena, 2024)
The Application Of The Talaqqi Method In Memorizing The Qur’an And Its Implications For The Power Of Memorization In Students In SMP Menara Al-Qur’an Parakan. This study aims to determine the implications of the use of the Talaqqi method in memorizing the Qur’an against the power of rote learning in SMP Menara Al-Qur’an. There are three main points in this study, namely: policy, steps, and implications of the Talaqqi method to the power of memorizing the Qur’an in SMP Menara Al-Qur’an Parakan. The researcher used an explorative qualitative approach to extract data from the chairperson of the foundation, caregivers, principals, teachers, students, and guardians of SMP Menara Al-Qur’an by the methods of observation, interviews, and documentation. As for data analysis techniques, researchers use inductive methods that depart from specific data to the public, namely collecting data and reviewing all data from varios primary sources in the field, then conducting the reduction of collected data written in the from of reports, focused and made systematic arrangements. The findings in this research are policies that provide space and create the work ethic of tahfidz teachers and students to improve the quality and quantity of memorization of the Qur’an in SMP Menara Al-Qur’an by making various breakthroughs in using appropriate methods for students with situations and conditions that exist. Keywords: Talaqqi Method, Power of Memorization, Memorization Al-Qur’an